Recent advances of injectable in situ-forming hydrogels for preventing postoperative tumor recurrence - Zhanpeng Wang; Bingtao Zhai; Jing Sun; Xiaofei Zhang; Junbo Zou; Yajun Shi; Dongyan Guo (Taylor & Francis Group, 2024)
The unavoidable residual tumor tissue from surgery and the strong aggressiveness of tumor cells pose challenges to the postoperative treatment of tumor patients, accompanied by in situ tumor recurrence and decreased quality of life. Therefore, there is an urgent need to explore appropriate postoperative therapeutic strategies to remove residual tumor cells after surgery to inhibit tumor recurrence and metastasis after surgery. In recent years, with the rapid development of biomedical materials, the study of local delivery systems as postoperative delivery of therapeutic agents has gradually attracted the attention of researchers. Injectable in situ-forming hydrogel is a locally administered agent injected in situ as a solution that can be loaded with various therapeutic agents and rapidly gels to form a semi-solid gel at the treatment site. This type of hydrogel tightly fills the surgical site and covers irregular excision surfaces. In this paper, we review the recent advances in the application of injectable in situ-forming hydrogels in postoperative therapy, focusing on the matrix materials of this type of hydrogel and its application in the postoperative treatment of different types of tumors, as well as discussing the challenges and prospects of its clinical application.